Implementation of guideline-directed medical treatment for ischemic heart disease management: A knowledge, attitude and practice based cross-sectional survey - Umm-e- Kalsoom; Amjad Khan; Syed Sikandar Shah; Ayesha Iqbal; Tahir Mehmood; Syed Mansoor Ahmed; Noshed Khan; Yu Fang (PLoS ONE, 2026)
Background Guideline-Directed Medical Therapy (GDMT) is central to managing ischemic heart disease (IHD), yet its implementation remains suboptimal in low- and middle-income countries (LMICs), including Pakistan. Aim This study assessed the knowledge, attitudes, and practices (KAP) of healthcare professionals (HCPs) toward GDMT and identified key barriers to its application. Methods A cross-sectional survey was conducted among HCPs including cardiologists and clinical pharmacists using a validated questionnaire. Data was collected from Punjab Institute of Cardiology, Lahore, Pakistan using convenience sampling. Descriptive statistics, t-tests, ANOVA, Mann–Whitney U, Kruskal–Wallis, and multiple linear regression analyses were used to evaluate KAP scores and their association with demographic and professional role. Statistical adjustment for multiple comparisons was done by Bonferroni correction. Results A total of 76 HCPs participated in the survey, comprising 42 cardiologists (55.3%) and 34 clinical pharmacists (44.7%). he overall mean knowledge score was 18.64 ± 2.02 out of 22 (84.7%). However, cardiologists (M = 19.54) scored significantly higher than clinical pharmacists (M = 17.52, p < 0.001); thus rejecting the null hypothesis. Knowledge scores were significantly higher among older professionals, those with postgraduate education, and clinic-based practitioners (p < 0.05). The average attitude score was 10.42 ± 2.06 out of 14 (74.4%), with younger professionals (aged 28–33), cardiologists, and postgraduates showing more favorable attitudes (p < 0.05). The mean practice score was 9.51 ± 2.55 (67.9%), with no significant differences by gender, role, or setting. Regression models showed age and profession significantly predicted knowledge, while attitude was influenced by education, experience, gender, and profession. Practice behaviors were not predicted by any demographic variables. Key barriers to GDMT implementation included limited consultation time (47.4%) and poor patient adherence (25%). Conclusion Although GDMT knowledge and attitudes were generally high among Pakistani cardiologists and clinical pharmacists, reported practice remained moderate. The results underscore the need for targeted educational interventions and system-level strategies to support consistent GDMT implementation.